Sosialisasi Produk Halal Dalam Islam Pada Perusahaan Limbah CV. Abinesia - Amir Salim; Muharir Muharir; Mahendra Mahendra (AKM, 2021)
Living things created by Allah SWT. created to continue to pray and prostrate to Him. An object or action is inseparable from five things, namely lawful, haram, syubhat, makruh, and permissible. Islamic principles regarding lawful and haram laws are basically all things permissible, while permitting and haram are the authority of Allah Almighty. The current phenomenon, the majority of Muslim humans no longer care about Halal and Haram matters, the priority is how humans can fulfill their life needs, both primary, secondary, as well as style and luxury.